Impacts of anthropogenic factors on fish community structure in Lebialem-Mone Forest Landscape of Cameroon - Ettagbor, Hans (2010)
Two sites of the Cross River within the Lebialem-Mone forest landscape of Cameroon were chosen, one of the sites faced with human activities (test site) and the other with no human pressure (control site). The lengths and weights of fish obtained from both sites were analyzed in SPSS. Fish communities living within these 2 sites were compared after collecting fish from them using gill nets within 2 months of sampling (September-October 2009). Questionnaires were distributed to the fishers to respond to questions related to their fishing practices. Each fish from a sample of 240 fishes obtained from both sites was identified with its length and weight recorded. Fishing pressure constitutes the main difference of these two sites with respect to the fish samples analyzed. Shannon index is also calculated for both sites to obtain the species diversity. The control site is comprised predominantly of large sized fish species while the test site is predominated by small sized fish species. Also, the control site has higher species diversity than the test site. Fishing and deforestation constitute the main factors affecting the fish communities on both sites as over 55 % of the river catchment in the test site has been deforested. However, fishing is the most dominant factor affecting the fishing community on this site due to the extremely high fishing pressure noticed. The survey carried out revealed that the fishers love to collect large size fish species. The total annual yield of fish obtained by the fisher population in this area is 167 633 kg within an area of about 8 hectares. The yield per unit effort (YPUE) is 14.5 kg of fish caught by each fisher per day.